Pertanggungjawaban Pihak Pengelola Usaha Dalam Perjanjian Penitipan Barang Perspektif Hukum Indonesia - Muhammad Wildan; Fatwa, Ahmad Fajrudin (Fakultas Hukum Universitas Mulawarman, 2024)
Storage services are public facilities that are beneficial for the party depositing the goods, but can also be detrimental to the party depositing the goods, due to the inconsistency of regulations with reality. This study uses normative law by using the theory of literature studies that examine books, scientific journals, legislation and relevant theories. In this case, regarding the responsibility of the business manager in the goods storage agreement from an Indonesian legal perspective in order to determine the form of rights, obligations, and responsibilities. This study aims to examine Indonesian law regarding its implementation so that it is appropriate, does not deviate and can have a good impact on the manager and the party depositing the goods.